Issues and challenges of Internet DNS security - Ning HU; Wen-ping DENG; Su YAO (网络与信息安全学报)
The domain name system is a critical component of the Internet infrastructure,which maps host names to IP ad-dresses and is involved in most Internet transactions.DNS security has a profound effect on the overall security of Internet and it is also a vital research content of Internet security.In order to improve the security capability of DNS,many enhanced protocols,monitoring mechanisms and best practices were proposed.But recent DNS attack events indicate there are still many recent major research challenges of DNS security problems.The existing achievements and challenges were summarized and discussed,which included security enhanced,behavior monitoring and privacy protection.